2019
DOI: 10.1038/s41598-019-46577-y
|View full text |Cite
|
Sign up to set email alerts
|

Density-based fractionation of soil organic matter: effects of heavy liquid and heavy fraction washing

Abstract: Physical fractionation methods used in soil organic matter (SOM) research commonly include density-based procedures with heavy liquids to separate SOM pools with varying turnover rates and functions. Once separated, the heavy SOM pools are often thoroughly rinsed with water to wash off any residues of the heavy liquids. Using four soils with contrasting properties, we investigated the effects of using either sodium polytungstate (SPT) or sodium iodide (NaI), two of the most commonly used heavy liquids, on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 25 publications
2
5
0
1
Order By: Relevance
“…This is within a typical range, as e.g. Baisden et al (2002) reported 89 ± 5%, Chenu and Plante (2006) reported 81-88% and Plaza et al (2019) reported 77-86.3%. Potential redistribution of particulate OM into mineral-associated fine fractions after physical fractionation was minimal as shown by C:N ratios of 8-9.5 of OM in mineral-associated fractions.…”
Section: Physical Fractionation and Carbon And Nitrogen Analysessupporting
confidence: 76%
“…This is within a typical range, as e.g. Baisden et al (2002) reported 89 ± 5%, Chenu and Plante (2006) reported 81-88% and Plaza et al (2019) reported 77-86.3%. Potential redistribution of particulate OM into mineral-associated fine fractions after physical fractionation was minimal as shown by C:N ratios of 8-9.5 of OM in mineral-associated fractions.…”
Section: Physical Fractionation and Carbon And Nitrogen Analysessupporting
confidence: 76%
“…Rinsing resulted in significant SOC extraction and thus SOC loss. This concurs with another study revealing critical changes in soils due to the use of sodium salts and rinsing (63). Therefore, we cannot recommend using Na-HMP as a fast and simple dispersion method.…”
Section: Limited Performance Of Chemical Dispersion With Sodium-hexametaphosphatesupporting
confidence: 89%
“…The following steps were performed: (i) 10 g of soil was shaken with 25 mL deionised water and 2 glass beads for 5 min at 80 rpm in 50 mL falcon tubes on an orbital shaker with the falcon tubes lying horizontally; (ii) wet sieving was performed using molecular sieves of 70 μm size that fit onto 50 mL falcon tubes, which accelerated the sieving process from >20 min per samples to <5 min (a larger cut-off than the typical 50, 53 or 63 μm was used since less water than for comparable wet-sieving methods was used and hence separation is less complete); (iii) the soil left on the sieve was washed back into the falcon tube with 12.5 mL of deionised water and the tube was vortexed for 2 s, then the sample was sieved again and the process was repeated, which resulted in a total water-to-soil ratio of 5:1 (50 mL of water to 10 g of soil); (iv) for separating POC and AggC sodium iodide adjusted to a density of 1.8 g cm −3 was used as recommended in Sohi et al (Sohi et al, 2001), who tested 1.6, 1.7 and 1.8 g cm −3 , and which is also used in the SOC model by Robertson et al (Robertson et al, 2019); (v) the samples were centrifuged to ensure the AggC fraction remains at the bottom of the tube; (vi) the POC and AggC fraction were separated by decanting the content of the tube after centrifugation onto a Whatman No. 2 filter paper through turning the tube by 360° while decanting; (vii) the filter paper was washed with deionised water, dried and weight to determine the POC fraction; (viii) the MAOC fraction was separated from the dissolved organic carbon fraction via centrifugation at 3000 rpm for 30 min (instead of using time-intensive vacuum filtration to <0.45 um) as suggested before (Robertson et al, 2019); (ix) to remove sodium iodide residues, the AggC fraction was washed with deionised water, though only once to avoid carbon loss (Plaza et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…(v) the samples were centrifuged to ensure the AggC fraction remains at the bottom of the tube; (vi) the POC and AggC fraction were separated by decanting the content of the tube after centrifugation onto a Whatman No. 2 filter paper through turning the tube by 360° while decanting; (vii) the filter paper was washed with deionised water, dried and weight to determine the POC fraction; (viii) the MAOC fraction was separated from the dissolved organic carbon fraction via centrifugation at 3000 rpm for 30 min (instead of using timeintensive vacuum filtration to <0.45 um) as suggested before (Robertson et al, 2019); (ix) to remove sodium iodide residues, the AggC fraction was washed with deionised water, though only once to avoid carbon loss (Plaza et al, 2019).…”
Section: Protocolmentioning
confidence: 99%